Assessment of late cardiotoxic effects in patients treated for cancer in childhood - Kincl, Vladimír; Panovský, Roman; Kepák, Tomáš; Bajčiová, Viera; Bednárová, Veronika; Opatřil, Lukáš; Máchal, Jan (Cancer medicine, 2022)
BACKGROUND: The most frequent chemotherapeutic regimens used in children's cancer contain anthracyclines, which may have potentially cardiotoxic effects even at a later point in time. Echocardiography including tissue Doppler imaging is well-proved noninvasive method to assess cardiac function. OBJECTIVES: To assess the late cardiotoxic effects in young adults treated for various cancer types in childhood. METHODS: Ninety-eight young adults who were treated for childhood cancer (CCS), median time 12.1 years after finishing the therapy, were comprised into study. All subjects underwent echocardiographic examination including tissue Doppler imaging. The echocardiographic parameters were compared to 57 healthy age-matched subjects. The CCS group also underwent 24-h ECG Holter monitoring to reveal any arrhythmias. RESULTS: The subjects in CCS group had lower E′ velocities from lateral (15.6 vs. 17.6 cm/s) and septal part (12.2 vs. 14.4 cm/s) of mitral annulus (p for both <0.001) and also lower S′ velocity from the tricuspid annulus (12.4. vs. 13.3 cm/s, p = 0.013) and tricuspid annulus peak systolic excursion (TAPSE; 22.2 vs. 23.9 mm, p = 0.017). There were no significant differences in left ventricular systolic velocities or ejection fraction. The occurrence of arrhythmias did not differ among subgroups of CCS with or without anthracycline therapy. CONCLUSION: Childhood cancer survivors had subclinical cardiac impairment in comparison with healthy controls, particularly in left ventricular diastolic function.
Keywords: Echocardiography; nádory; Young Adult; mladý dospělý; Electrocardiography, Ambulatory; kardiotoxicita; elektrokardiografie ambulantní; Humans; lidé; Cardiotoxicity; echokardiografie; Neoplasms